Modeling hydration of cementitious systems - Riding, Kyle A.; Poole, Jonathan L.; Folliard, Kevin J.; Juenger, Maria C. G.; Schindler, Anton K. (My University, 2012)
Concrete performance, including strength, susceptibility to delayed ettringite formation, and residual stress development are dependent on early-age temperature development. Concrete temperature prediction during hydration requires an accurate characterization of the concrete adiabatic temperature rise. This study presents the development of a model for predicting the adiabatic temperature development of concrete mixtures based on material properties (for example, cement chemistry and fineness and supplementary cementitious materials (SCM) chemistry), mixture proportions, and chemical admixture types and dosages. The model was developed from 204 semi-adiabatic calorimetry results and validated from a separate set of 58 semi-adiabatic tests. The final model provides a useful tool to assess the temperature development of concrete mixtures and thereby facilitate the prevention of thermal cracking and delayed ettringite formation in concrete structures.
Keywords: Calorimetry; Heat of hydration; Modeling